Conduction disturbances after transcatheter aortic valve implantation procedures – predictors and management - Wilczek, Krzysztof; Reguła, Rafał; Bujak, Kamil; Chodór, Piotr; Długaszek, Michał; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Transcatheter aortic valve implantation (TAVI) has become a safe and efficient alternative to cardiac surgery in patients with severe aortic stenosis. In many countries the number of performed TAVI procedures equals the number of surgical implantations. Indications for TAVI are becoming more liberal, allowing a wider spectrum of patients to benefit from the advantages of transcatheter therapy. Due to its invasive nature, TAVI is associated with some complications such as conduction disturbances. Although these disturbances are usually not lethal, they have a great influence on patients’ state and long term-survival. The most relevant and common are His’ bundle branch blocks, atrioventricular blocks, and need for permanent pacemaker implantation. With the frequency at 10% to even 50%, conduction abnormalities are among the most important TAVI-related adverse events. Risk factors for conduction disturbances include age, anatomy of the heart, periprocedural factors, type of implanted valve, and comorbidities. Severity of occurring complications varies; therefore selection of a proper treatment approach is required. Considered as the most effective management, permanent pacemaker implantation turned out to negatively influence both recovery and survival. Moreover, there is no expert consensus on use of resynchronization therapy after TAVI. In this paper, the authors present a comprehensive analysis of the most common conduction disturbances accompanying TAVI, factors related to their occurrence, and treatment approach.